PENGGUNAAN LEADCAP SEBAGAI MATERIAL ADITIF UNTUK WARM MIX ASPHALT (WMA) - Muhammad rifki hanifan; Apriadi Simon Harianja; Bagus Hario Setiadji; YI. Wicaksono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Material LEADCAP is an additive material to be added to the asphalt (by the dry/ wet process) for the purpose of reducing the temperature of the mixed asphalt. LEADCAP melts at about 100̊C and completely dissolve into the asphalt at a temperature 130⁰C. To determine the performance of the asphalt mixture by LEADCAP, we made 15 samples to determine the optimum bitumen content (OBC) with a bitumen content of 4.5%, 5%, 5.5%, 6%, 6.5%. Then with the OBC has been obtained, the mixture is made with 3 variations LEADCAP levels of 2%, 4%, and 6%. From the LEADCAP levels, made respectively - each 3 variations in temperature is 145⁰C, 140⁰C, 130⁰C. Every each temperature we made 3.